Pengaruh Karakteristik Individu Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Dinas Perumahan Dan Kawasan Pemukiman Kabupaten Tapanuli Tengah - Ratri Dwi Aryani; Rosmita Ambarita; Tiurlina Hasmawati (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of individual characteristics and work environment on employee performance at the Department of Housing and Settlement Areas of Central Tapanuli Regency. The research method used is a quantitative method with a descriptive approach. The population in this study consisted of 62 employees, and all were selected as the sample using a saturated sampling technique. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was conducted using classical assumption tests, including normality, heteroscedasticity, and multicollinearity tests, as well as multiple linear regression analysis, correlation coefficient, coefficient of determination, t-test (partial), and F-test (simultaneous). The results show that individual characteristics and work environment simultaneously have a positive and significant effect on employee performance, with an F-value of 52.568 > 4.00 and a significance value of 0.000 < 0.05. Partially, individual characteristics have a positive and significant effect on employee performance with a t-value of 2.110 > 1.670 (sig. 0.039 < 0.05), while the work environment has a stronger positive and significant effect with a t-value of 10.113 > 1.670 (sig. 0.000 < 0.05). The coefficient of determination (R²) is 0.641, indicating that 64.1% of employee performance variation is explained by individual characteristics and work environment, while the remaining 35.9% is influenced by other variables not examined in this study. The regression equation obtained is KP = 4.716 + 0.155(IC) + 0.676(WE) + e, indicating that improvements in individual characteristics and work environment will enhance employee performance.